2022
DOI: 10.3389/fpsyt.2022.876761
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Personal Recovery Construct in Bipolar Disorders: Definition, Usage and Measurement. A Systematic Review

Abstract: Personal recovery from psychiatric disorders is a journey toward a satisfying and hopeful life despite the possible persistence of symptoms. This concept has gained interest and become an increasingly important goal in mental health care programmes. Personal Recovery is well described in the context of severe mental illnesses in general, but little is known about this journey in bipolar disorders and the factors underlying it. A systematic review was conducted according to the PRISMA recommendations, focusing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 49 publications
(107 reference statements)
2
9
0
Order By: Relevance
“…Our findings support a theory of personal recovery as a global construct. This is a significant finding because personal recovery, although viewed as a broad concept, is often assessed as multiple interrelated factors without recognizing a higher order nature (e.g., Chirio-Espitalier et al, 2022). Our findings indicate that suicide personal recovery is a unified construct, consisting of Self-Worth, Life Worth, Social Worth, and Self-Understanding as lower order correlated factors (Sokol et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings support a theory of personal recovery as a global construct. This is a significant finding because personal recovery, although viewed as a broad concept, is often assessed as multiple interrelated factors without recognizing a higher order nature (e.g., Chirio-Espitalier et al, 2022). Our findings indicate that suicide personal recovery is a unified construct, consisting of Self-Worth, Life Worth, Social Worth, and Self-Understanding as lower order correlated factors (Sokol et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Two recent systematic reviews have helped to specify the characteristics of personal recovery (PR) in BD (Chirio-Espitalier et al, 2022 , Jagfeld et al, 2021 ). The review of Chirio-Espitalier and colleagues showed that PR is intimately linked with metacognitive relationships maintained with mood fluctuations including resilience and decreasing of hypervigilance.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 However, a growing body of evidence suggests that this symptom-centered approach may not fully address the complexities and holistic needs of individuals living with BD 7 and people with BD have shown their dissatisfaction with this model, exhibiting interest in taking control of their lives rather than returning to the elusive state of the premorbid level of functioning. 8 According to Merikangas et al, 1 BD is responsible for the loss of more disability-adjusted life-years than all forms of cancer or major neurologic conditions, which has a marked effect on the overall quality of life (QoL) of both patients and their families. 9 Consequently, mental health is witnessing a paradigm shift towards embracing a personal recovery-focused model, which encompasses pursuing a satisfying and meaningful life, even when clinical symptomatology is present.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 This concept has become increasingly important and is seen as a desired outcome for mental health care programs in severe mental disorders, specifically for BD. 8 Recovery is described as a personal journey of coping with mental illness, which involves a series of subjective experiences and, therefore, is based on the person's empowerment, self-directedness and perception of competence to deal with their difficulties. 12 Hence, considering the significant impact that BD has on various aspects of daily life (i.e., work productivity, interpersonal relationships, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation